2007
DOI: 10.1111/j.1440-1827.2007.02085.x
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting aneurysms involving both anterior cerebral artery and aorta

Abstract: Non-traumatic intracranial dissecting aneurysm (IDA) has been recently reported with increasing frequency and is recognized as a possible cause of subarachnoid hemorrhage. However, the pathogenesis of this disease is still unclear. Cystic medial necrosis (CMN) is known to be a cause of aortic dissection, especially in Marfan's syndrome. Presented herein is the case of a 49-year-old man who had IDA of the right anterior cerebral artery and abdominal aortic dissection without Marfan's syndrome. Histological exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Thus it was 32% (8/25) in AD compared with 20.3% (27/133) in the AA group, and these patients had no comorbidity. In contrast to the AA group, there were few case reports of concurrent IAs in patients with ADs, all of which were associated with Marfan's syndrome 16 17. Some authors reported that the prevalence of IAs in patients with coarctation of the aorta was >10% 18 19.…”
Section: Discussionmentioning
confidence: 99%
“…Thus it was 32% (8/25) in AD compared with 20.3% (27/133) in the AA group, and these patients had no comorbidity. In contrast to the AA group, there were few case reports of concurrent IAs in patients with ADs, all of which were associated with Marfan's syndrome 16 17. Some authors reported that the prevalence of IAs in patients with coarctation of the aorta was >10% 18 19.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, some authors [5][6][7] have published the link between IA and aortic aneurysm, which showed an IA incidence of 9%-11% in patients with aortic aneurysms. However, there are a limited number of genetic or experimental studies [8][9][10] and case reports [11][12][13] for the association between IA and aortic dissection (AD).…”
mentioning
confidence: 99%
“…In this case, the aneurysms were observed in the abdominal aorta as well as in the intracranial arteries on the A3 segment of the ACA and at the bifurcation of the MCA. A previous report [10] suggested that coexistence of dissecting aneurysms in the ACA and abdominal aorta was related to the pathological findings of medial degenerative changes with the accumulation of acid mucopolysaccharides. IAs and AAA, however, result from different underlying disease processes, and thus have different risk factors [2].…”
Section: Discussionmentioning
confidence: 99%